Reconceptualizing the "Publicness" of Public Housing: The Case of Brussels - Aernouts, Nele (Social Inclusion, 2015)
This article brings together various spatial and political theorizations on the commons as a broader project to understand multiple dimensions of the inclusive nature of public housing. By picking up theorizations on the commons, the article feeds the debate on the loss of “publicness” of public housing and removes attention from what is seen as a state related business. Four core-dimensions are identified: ownership, participation, community activity and physical configuration. The article takes a sample of public housing estates in the Brussels capital region as case studies to test the capacity of this framework to detect the degree of “publicness” of various forms of public housing. The preliminary results—based on this limited sample of cases studied through interviews with privileged informers and a literature study—suggest that approaches where individual households are actively involved in the organization of the dwelling environment work best to compensate for the loss of “publicness” that has occurred since the decline of the welfare state. In that respect, these approaches tie in with some early predecessors of “public” housing, mainly cooperatively organized garden city developments. Further in-depth case study research should shed more light on the validity of this hypothesis, as well as on the precise mechanisms and features that determine this regained “publicness”.